Geography, Urbanisation and Settlement Patterns in the Roman Near East - MacAdam, Henry Innes, author.
1 online resource
Keywords: "This title was first published in 2002: This volume focuses on the Roman provinces of Syria and Arabia, above all the lands now within Lebanon, Syria and Jordan. The first articles look at questions of geography, cartography and toponymy, particularly in Strabo, Pliny and Ptolemy. The following sections are concerned with settlement patterns and urban development in the region. In the Roman and early Byzantine periods, the inland areas underwent a gradual transformation, from a semi-sedentary, lightly populated and predominantly rural region, to one of large cities and a network of prosperous, socially sophisticated villages, linked by a network of roads. That change is documented by a wealth of epigraphy from both the urban communities and their outlying settlements (the subject of several articles). By the 4th century, too, Christianity had become the dominant religion and remained such until the arrival of Islam."--Provided by publisher.